Oxidant-Antioxidant Balance in Severe Brain Injury - N. N. Yepifantseva; T. I. Borshchikova; Yu. A. Churlyaev; I. K, Ratkin; N. V. Nikiforova; S. A. KlochkovaAbelyants; L. G. Kheringson (Общая реаниматология, 2010)
Objective: to study the time course of changes in oxidative status parameters and their relationship with inflammation mediators in the acute period of severe brain injury (SBI). Subjects and methods. One hundred and thirteen patients aged 17—67 years were examined. The injury was closed and open in 54 (47.8%) and 59 (52.2%) patients, respectively. Severe brain contusions were observed in 47 patients, diffuse axonal lesions were seen in 2, and intracranial hematomas were present in 64 patients. The Glasgow coma scores for admission consciousness loss were 6.8±0.25. A control group comprised 23 healthy individuals. The significance of differences was estimated by Student’s test, Wilcoxon-Mann-Whitney, test, Spearman’s correlation test. Venous blood samples were used to study total oxidative activity (TOA) and total antioxidative activity (TAA), diene conjugates, lactic acid, albumin, transferrin (TF), ceruloplasmin, C-reactive protein, and lactoferrin (LF) were measured in venous blood on disease days 1, 4, 7, 10, 14, and 21. The profile of plasma cytokines (IL-1j8, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12p70, TNF-а, and IFN-y) was studied by flow fluorometry on a Cytomics FC 500 cytofluorometer (Beckman Counlter, USA) (reagents were from Bender Medsystems, Austria). Results. In SBI, there was an increase in oxidants, a reduction in antioxidant activity, and lipid peroxidation activation, which were closely related. The oxidation coefficient (TOA/TAA) was 40 times greater than the normal values on days 7 to 10. The oxidation parameters were found to be associated with inflammation and cytokine-mediated immunological reactions. The time course of changes in the study proteins was characteristic for systemic inflammation and there was an association with oxidative processes only for ceruloplasm. TF was found to have an association with IL-5 and IL-10, which reflects its involvement in immunological reactions. The association with hypoxia was established for IL-6 and LF. Ihe elevation or LF was directly caused by the neutrophil activating factor IL-8. Conclusion. Oxidative stress is an important factor in impairing hemostasis in SBI. The processes of oxidation and antioxidation are associated with inflammation and cytokine-mediated immunological reactions. Key words: severe brain injury, oxidative stress, cytokines, acute inflammation phase proteins.